Galectin-9 in cancer therapy: from immune checkpoint ligand to promising therapeutic target - Zhang, Minpu; Liu, Cun; Li, Ye; Li, Huayao; Zhang, Wenfeng; Liu, Jingyang; Wang, Liquan; Sun, Changgang (Frontiers in Cell and Developmental Biology, 2024)
Galectin-9 (Gal-9) is a vital member of the galectin family, functioning as a multi-subtype galactose lectin with diverse biological roles. Recent research has revealed that Gal-9's interaction with tumors is an independent factor that influences tumor progression. Furthermore, Gal-9 in the immune microenvironment cross-talks with tumor-associated immune cells, informing the clarification of Gal-9's identity as an immune checkpoint. A thorough investigation into Gal-9's role in various cancer types and its interaction with the immune microenvironment could yield novel strategies for subsequent targeted immunotherapy. This review focuses on the latest advances in understanding the direct and indirect cross-talk between Gal-9 and hematologic malignancies, in addition to solid tumors. In addition, we discuss the prospects of Gal-9 in tumor immunotherapy, including its cross-talk with the ligand TIM-3 and its potential in immune-combination therapy.Galectins (Gals) are a family of lectins defined by a shared amino acid sequence. Their structure features a carbohydrate recognition domain (CRD) that specifically binds to polysaccharides containing β-galactoside. This structural feature serves as a foundation for understanding the function of such sugar chain-binding proteins [1]. Apart from recognizing the typical glycan structure, each member of the Gals family exhibits preferential binding to specific glycosylated proteins and/or lipids found on the cell surface or in the extracellular matrix [2,3]. This specific binding influences the interaction between Gals and human cells. There are 16 identified Gals that exert both intracellular and extracellular effects. They are involved in various biological functions, including the regulation of cell growth, apoptosis, pre-mRNA splicing, cell-cell and cell-matrix adhesion, cell polarity, and innate/acquired immunity. These functions may be linked to the relationship between Gals and glycated proteins and/or lipids (The figure is depicted in Figure 1)